Factors Influencing the Implementation of SAK EMKM to Msmes in Kesugihan District, Cilacap Regency - Suwono; Muhamad Rijal Pamungkas; Hatta Setiabudhi (MultiTech Publisher, 2023)
This research aims to examine the influence of socialization of SAK EMKM, understanding of accounting and educational level on the implementation of SAK EMKM. The focus of this study is on MSME owners in Kesugihan District, Cilacap Regency. A total of 70 data were collected using survey method with purposive sampling technique. The tool used to analyze the variable relationships in this study is Partial Least Squares (PLS) with SmartPLS implementation. Research results show that educational level does not affect the implementation of SAK EMKM. On the other hand, different understandings of financial reporting and the socialization of SAK EMKM affect the implementation of SAK EMKM